Identification and Ranking of Core Values in Family Medicine: A Mixed Methods Study From Ukraine - Kolesnyk, Pavlo; Bayen, Sabine; Shushman, Ivanna; Kolesnyk, Andrew; Kuodza, George; Klemenc-Ketiš, Zalika; Frese, Thomas (Frontiers in Medicine, 2021)
Introduction/Context: The term core value (CV) can be defined as fundamental beliefs or principles, guiding one's behavior in a social context. Though core competencies of family medicine (FM) have been clearly defined by WONCA, there has been an ongoing debate on what the CVs are for family doctors (FDs). Ukraine is a developing country in the middle of Europe with a population of 43 million inhabitants, gained independence from the Soviet Union in 1991. Ukraine is a low-income country, developing a modern European healthcare system, especially regarding FM. To implement WONCA standards, it is mandatory to assess the ongoing understanding of CVs in clinical daily practice among active FDs, working in different countries of Europe including Ukraine. Research questions: How do Ukrainian FDs (Delphi group experts) define the CVs of FM in Ukraine and how important are these CVs to a wider population of Ukrainian FDs in their everyday practice? Methods: A mixed method study was conducted in two steps during August and September 2020 in Ukraine. The first part was a qualitative Delphi round (three rounds) design among 20 Ukrainian FDs who were familiar with teaching and terms like CV. A consensus list of six CVs has emerged from the Delphi round study. The second part was a quantitative survey among Ukrainian FDs, who were not specially used to discussing CVs. The consensus list of those six CVs was then submitted to 2000 FDs (randomly selected) who were not involved in the Delphi team, to rank those values from one to nine, according to the importance from their personal point of view. Demographic characteristics have been assessed for all the participants of the Delphi round and quantitative survey. Results: Twenty FDs were involved as experts in the first Delphi round, whereas only five experts continued their participation in the second and the third rounds of the survey. The following six CVs emerged from the Delphi round: comprehensive approach, care coordination, first recourse, continuity of care, integrated approach, and patient and family centered care. The final sample consisted of 375 FDs (19% response rate). There were 323 (88.7%) female and 34 (9.3%) male FDs in the sample. The mean age of the participants was 44.6±13.5 years. Discussion/Conclusion: Defining CVs for FM by Ukrainian FDs in a given socio-economical and historical-cultural setting is crucial to optimize primary medical care and to guarantee an appropriate and successful implementation of WONCA standards as well as CVs in different countries including those where reformation of the health system is ongoing.